Formation of network coding coalitions for cooperative communications. Issue 2 (1st June 2014) - Li, Dapeng; Zhong, Wei
Abstract : Recent results have shown that employing NC may have an adverse effect and dimmish the advantage of NC in CC because of the existence of NC noise. The authors propose space network‐ coded cooperation (SNCC) in which sources transmit in turn, and relays overhear and process the data they have received from different sources. Then, they broadcast the coded data to corresponding destinations in a single time instance. In this spirit, NC can be viewed as being performed in the space, and each destination can average the NC noise that comes from different relays. The authors derive a closed‐form expression for the NC noise of SNCC, and show that SNCC has a potential to significantly reduce the NC noise if sessions in the network are well organised into disjoint groups/coalitions to use SNCC. Towards the end, the formation of SNCC coalitions is interpreted as a coalition formation game. Algorithms are proposed to get the solution of the game. Finally, through numerical simulations, the authors demonstrate the effectiveness of the proposed SNCC scheme and algorithms in achieving a high spectrum efficiency for CC.